2001
DOI: 10.1159/000049986
|View full text |Cite
|
Sign up to set email alerts
|

New Compound Heterozygous Mutation in the <i>CYP17</i> Gene in a 46,XY Girl with 17α-Hydroxylase/17,20-Lyase Deficiency

Abstract: Background: 17α-Hydroxylase/17,20-lyase deficiency is caused by a defect of P450c17 which catalyzes both 17α-hydroxylase and 17,20-lyase reactions in adrenal glands and gonads. Results: In the present study, we analyzed the CYP17 gene in a Japanese patient with 17α-hydroxylase/17,20-lyase deficiency. The patient was a phenotypic girl and referred to us for right-sided inguinal hernia at the age of 4 years. Biopsy of the herniated gonad showed testicular tissue. The karyotype was 46,XY. At 6 years of age, hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…This condition is considered a disorder of sex development (DSD), which causes lack of virilization in 46, XY individuals [2]. Patients with 17OHD account for nearly 1% of all CAH cases, and at least 56 mutations have been described in the CYP17A1 gene [3][4][5][6][7]. The lack of adrenal 17α-hydroxylase activity leads to massive overproduction of mineralocorticoids (e.g., 11-deoxycorticosterone and corticosterone), promoting hypertension and hypokalemia [3].…”
Section: Introductionmentioning
confidence: 99%
“…This condition is considered a disorder of sex development (DSD), which causes lack of virilization in 46, XY individuals [2]. Patients with 17OHD account for nearly 1% of all CAH cases, and at least 56 mutations have been described in the CYP17A1 gene [3][4][5][6][7]. The lack of adrenal 17α-hydroxylase activity leads to massive overproduction of mineralocorticoids (e.g., 11-deoxycorticosterone and corticosterone), promoting hypertension and hypokalemia [3].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of mutations of the CYP17 gene reported to date have been associated with combined 17␣-hydroxylase/17,20-lyase deficiency [9][10][11][12][13][14][15][16][17][18][19][20][21], and most muta- tions have been localized within the coding region of the CYP17 [9][10][11][12][13][14][15][16][17][18][19][20][21]40]. Studies on naturally occurring and synthetic P450c17 mutants have shown that amino acid residues, which are predicted to participate in the heme-binding region or hydrophobic active site play a crucial role, although other residues may be also important in enzyme activity [15,21,24,29].…”
Section: Discussionmentioning
confidence: 99%
“…The human CYP17 is expressed in the adrenals and gonads and, therefore, genetic disorders of this gene affect both the adrenal and gonadal steroidogenesis [7,8]. Mutations of the CYP17 gene cause 17-hydroxylase/17,20-lyase deficiency (OMIM 202110) [9][10][11][12][13][14][15][16][17][18][19][20], which is a rare form of congenital adrenal hyperplasia (CAH) occurring in about 1% of all CAH patients. The impaired production of cortisol in zona fasciculata leads to hypersecretion of ACTH, which stimulates the synthesis of the weak mineralocorticoids 11-deoxycorticosterone (DOC) and corticosterone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations